The Effect of different storage temperatures on complement protein (C3 and C4) levels: a single-centre study - Hanif, Hamna Muhammad; Areej Fatima; Sidra Abdul Jabbar; Sabiha Anis (Journal of the Pakistan Medical Association, 2026)
Objectives: To compare the effect of storage at 2-8°C and -40°C on temperature-sensitive serum complement protein levels, and to determine the optimal storage temperature that preserves sample integrity during transportation and storage. Method: The comparative, laboratory-based, experimental study was conducted at the Immunology Laboratory, Indus Hospital and Health Network, Karachi, from August to November 2022. At the collection point, after centrifugation, a portion of each serum sample was transferred to a separate aliquot and frozen at -40°C, while the remaining serum was retained in the original tube at 2-8°C. Samples were transported to and stored in the laboratory at the same temperatures. They were assayed for temperature-sensitive serum complement proteins 3 and 4 by turbidimetry. Data was analysed using SPSS 21. Result: There were 50 samples that were analysed. Coefficient of variation at the two temperatures was within 8% for 47(94%) C3 (p=0.730) and 46(92%) C4 (p=0.964) levels. Kappa coefficient value was 0.90 for C3, indicating near-perfect agreement, and it was 1.0 for C4, indicating perfect agreement. There was no clear trend of change in the coefficient of variation pattern of either analyte with a change in storage time of samples at the collection point. Conclusion: Values for complement proteins 3 and 4 were not significantly different for samples stored at 2-8oC or -40oC. Key Words: Complement system proteins, Temperature-sensitivity, Sample integrity, Temperature, Turbidimetry.